Unicystic Ameloblastoma: Case Report - Hernández-Rivera DDS, MAE, Patricia; Castro-Mora DDS, Msc, Sergio; Jiménez-Araya DDS, Manuel (Odovtos - International Journal of Dental Sciences, 2016)
Unycistic ameloblastoma is a type of ameloblastoma that clinic, radiographic and macroscopic signs suggest a cyst, but histologically shows ameloblastic characteristics. However, it differs from the solid type, in that the former presents in younger patients and it is less aggressive. This case was asintomatic and associated with a mandibular third molar, which had a radiolucent circumscribed in the distal zone, compatible with follicular space; but the histologic study clarified the diagnosis.